(untitled) (AUN INTERNATIONAL CONFERENCE, 2025)
Global food security is increasingly challenged by climate change, population growth, and resource constraints. Soil organic carbon (SOC) storage results from a balance of plant residues, root exudates microbial decomposition, governed by both biological and physical processes. Agricultural practices strongly influence these mechanisms. Conventional tillage and synthetic fertilization tend to deplete SOC and damage soil structure and biodiversity. This paper explores the role of organic fertilizers, Soil Carbon Storage and Strategic Land Management in enhancing soil health and promoting sustainable agriculture. It enumerates how organic amendments like biochar, manure, fermented grass, growing of cover crops, diversified crop rotation can improve soil's physical, chemical, and biological properties. These practices promote the growth and diversity of beneficial soil microorganisms, which are crucial for nutrient cycling and soil stability. Additionally, the combination of new innovations in organic fertilizers may improve soil health and agricultural yield, without any detrimental impacts on the environment and soil, ensuring sustainable food production, safety, and security.